Identification of Significant Modules and Targets of Xian-Lian-Jie-Du Decoction Based on the Analysis of Transcriptomics, Proteomics and Single-Cell Transcriptomics in Colorectal Tumor - Yu CT; Chen T; Lu S; Hu W; Zhang Q; Tan J; Sun D; Li L; Sun X; Xu C; Lai Y; Fan M; et al. (Dove Medical Press, 2022)
Cheng-Tao Yu,1,* Tongqing Chen,1,* Sicheng Lu,1,* Wenlong Hu,1 Qinchang Zhang,1 Jiani Tan,1 Dongdong Sun,1 Liu Li,1 Xin Sun,1 Changliang Xu,1 Yueyang Lai,1 Minmin Fan,1 Zhengjie Shen,2 Weixing Shen,1 Haibo Cheng1 1The First Clinical Medical College, Jiangsu Collaborative Innovation Center of Traditional Chinese Medicine Prevention and Treatment of Tumor, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China; 2Medical Oncology Department, The Affiliated Zhangjiagang Hospital of Soochow University, Suzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Weixing Shen; Haibo Cheng, The First Clinical Medical College, Jiangsu Collaborative Innovation Center of Traditional Chinese Medicine Prevention and Treatment of Tumor, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China, Tel +86 13815857118, Fax +86 2585811006, Email haibocheng@njucm.edu.cn; weixingshen@njucm.edu.cnPurpose: Colorectal cancer (CRC) remains the third most common tumor worldwide. Ulcerative colitis (UC) could cause chronic inflammation and ulcers in the colon and rectum. UC is a risk factor for a high incidence of CRC, and the incidence of UC-associated CRC (UC-CRC) is still increasing. Chinese medicine prescription, Xian-Lian-Jie-Du decoction (XLJDD), has been proven its efficacy in some UC-CRC patients. However, the mechanism of XLJDD in treating UC-CRC remains unknown. This study aimed to investigate the mechanism of XLJDD in treating UC-CRC.Methods: We constructed an AOM/DSS mouse model that could simulate the various stages of UC-CRC in humans. XLJDD and its 5 main components are used to treat the AOM/DSS model, respectively. With the power of high-throughput sequencing technology, we described the mechanism of XLJDD from transcriptomics, proteomics, and single-cell transcriptomics.Results: Our results showed that XLJDD could effectively suppress the occurrence and development of colorectal tumors. Using the weighted correlation network analysis (WGCNA), several mRNA and protein modules that respond to XLJDD have been identified. Moreover, two essential genes, Mfsd2a and Ccdc85c, were caught our attention. They were prognostic markers in CRC patients, and their expression could be significantly modulated by XLJDD, showing their potential as effective targets of XLJDD. In addition, we also discovered that XLJDD could affect the cell composition of the colorectal tumor environment, especially in the infiltration of B cells.Conclusion: We demonstrated that XLJDD could prevent the initiation and development of colorectal tumors by modulating the expression of Mfsd2a and Ccdc85c and reducing the infiltration of B cells in the tumor microenvironment of colorectal tumor.Keywords: colorectal tumor, Mfsd2a, Ccdc85c, inflammation pathway, B cell infiltration